Modeling dusty star forming galaxies: connections to protoclusters and massive quiescents - Araya, Pablo Andrés Araya (2025)
The study of massive galaxies in the early Universeboth actively star-forming and quiescentchallenges our current understanding of galaxy formation and evolution. In particular, dusty star-forming galaxies (DSFGs) and massive quiescent galaxies (MQs) at high redshift represent extreme populations whose physical properties, number densities, and evolutionary pathways remain difficult for theoretical models to reproduce. Recent observations, especially from ALMA and JWST, have increased tensions between theory and observational data, highlighting the need for improved modeling frameworks. This thesis addresses these challenges using the \\texttt semi-analytic model (SAM) to explore the environmental dependence, physical origins, and potential evolutionary connection between DSFGs and MQs across cosmic time. First, we investigate the relationship between DSFGs and galaxy protoclusters by assigning submillimeter (submm) fluxes to simulated galaxies via scaling relations derived from radiative transfer calculations. We find that protocluster cores host an excess of submm-bright galaxies compared to less dense environments, primarily due to an overrepresentation of massive, star-forming galaxies driven by the underlying dark matter distributioncontrary to conventional wisdom of enhanced starburst activity. These findings provide a theoretical basis for the observed spatial association between DSFGs and protoclusters and offer new insights into early environmental effects on galaxy evolution. Next, we address the long-standing challenge of simultaneously reproducing submm number counts (DSFGs) and the number densities of MQs at $z \\gtrsim 3$. Using the Markov Chain Monte Carlo (MCMC) calibration mode of \\texttt, we test various combinations of observational constraints. We identify a model that successfully reproduces the observed submm number counts while remaining consistent with lower limits on MQ number densities. This solution requires enhanced star formation efficiency during merger-driven events and a black hole accretion model independent of halo mass, enabling rapid growth of both stellar mass and SMBHs. The results from this work also emphasize the importance of robust calibration techniques for addresing the highly degenerate parameter space of galaxy formation models. Finally, we used the re-calibrated model from previous work to investigate the potential evolutionary connection between DSFGs and MQs. We find that while most high-$z$ MQs were submm-bright (DSFGs) in the past, a significant fraction of DSFGs do not evolve into MQs by $z \\gtrsim 2$, due to their diverse evolutionary pathways. We further analyze the physical mechanisms that quench star formation in MQ progenitors and typical DSFGs, showing that star formation history, merger activity, and AGN feedback collectively shape their evolution. Together, these results advance our understanding of extreme galaxy populations in dense environments and demonstrate how robustly calibrated SAMs, despite their simplicity, can bridge the gap between observations and theory in the era of deep, high-resolution surveys.